Hidden resources: Non-timber forest products for livelihood improvement and biodiversity conservation: Documenting Kenyan experiences - Agromisa; Technical Centre for Agricultural and Rural Cooperation; Pelum Kenya (Agromisa, 2009)
The case-studies in this manual present a number of innovative approaches to environmental management, particularly in woodland areas threatened by aridity. The studies document the way communities living near woodlands developed non-timber forest products that have improved their livelihoods and helped to conserve biodiversity. The book provides useful information for communities living and working in similar agro-ecological areas.